2008
DOI: 10.1002/app.28066
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinkable poly(vinyl acetate)/clay nanocomposite films cast from soap‐free emulsion‐polymerized latices

Abstract: Exfoliated poly(vinyl acetate) (PVAc)/ montmorillonite (MMT) and poly(vinyl acetate-co-glycidyl methacrylate) [P(VAc-co-GMA)]/MMT nanocomposite latices, prepared by soap-free emulsion polymerization, were able to be cast into films, and the latter was crosslinked with diethylene triamine as a curing agent. The glass-transition temperature of the crosslinked P(VAc-co-GMA)/ MMT nanocomposite films was higher than that of the PVAc/MMT counterparts. Although both the Young's modulus and yield stress for the PVAc/M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 26 publications
1
19
0
2
Order By: Relevance
“…This phenomenon coincided with the results of XRD and FTIR. All these particles were round or approximately round, randomly dispersed, not as platelets in a flat form uniformly dispersed as described by Chien et al 19,20 In addition, a "strawberry" structure was also observed in the dispersion; this structure was first mentioned by Sinha Ray and coworkers 26,27 . As shown in Fig.…”
Section: Dispersion and Particlesmentioning
confidence: 75%
See 1 more Smart Citation
“…This phenomenon coincided with the results of XRD and FTIR. All these particles were round or approximately round, randomly dispersed, not as platelets in a flat form uniformly dispersed as described by Chien et al 19,20 In addition, a "strawberry" structure was also observed in the dispersion; this structure was first mentioned by Sinha Ray and coworkers 26,27 . As shown in Fig.…”
Section: Dispersion and Particlesmentioning
confidence: 75%
“…Water or other organic molecules can enter into the layers of MMT, leading to its expansion through absorbing water, high dispersion, and adsorption, causing it to easily make mud, which can be activated, organized, and modified. The application of PVAc has been reported previously: PVAc MMT prepared by emulsion polymerization in the presence of poly(vinyl pyrrolidone) (PVP) 14,15 or in the presence of anionic surfactants, 16 preparation of PVAc MMT PVA, 17,18 preparation of PVAc MMT cross-linked by glycidyl methacrylate (GMA), 19,20 and preparation of PVAc MMT initiated by γ -ray radiation intercalation polymerization and the coblending of PVAc MMT with high-density polyethylene. 21,22 The previous studies on PVAc MMT suggest that other additives or agents as main components are necessary for the synthesis, such as PVP, PVA, GMA, and anionic surfactants as mentioned above.…”
mentioning
confidence: 99%
“…The presence of MMT-DOAB did not have any significant effect on the formation of latex particles. These all particles were round or similarly round, as platelets in a flat form but not uniformly dispersed as described by Chien and coworkers 23,24 The size of MMT-DOAB aggregations was about 0.1-10 μm. They comprised some elementary particles (also called "structural units"), which were constituted by some thin solid layers.…”
Section: Dispersionmentioning
confidence: 85%
“…The presence of MMT had no significant effect on the formation of latex particles. These particles were all round or similarly round, and dispersed randomly together, as platelets in flat form but not uniformly dispersed as described by Chien et al 19,20 Rheology The liquid samples of PVAc and PVAc-MMT were tested using an NDJ-1 rotary viscometer under shear rates c of 0?63, 1?26, 3?14 and 6?28 s 21 respectively. The apparent viscosity g (mPa s) ( Table 1) decreased with an increase in shear rate, indicating that PVAc and PVAc-MMT both were pseudoplastic non-Newtonian fluids.…”
Section: Resultsmentioning
confidence: 99%